2023
DOI: 10.1186/s12974-023-02758-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of admission neutrophil serine proteinases levels with the outcomes of acute ischemic stroke: a prospective cohort study

Abstract: Background Neutrophil serine proteinases (NSPs), released by activated neutrophils, are key proteins involved in the pathophysiologic processes of stroke. NSPs are also implicated in the process and response of thrombolysis. This study aimed to analyze three NSPs (neutrophil elastase, cathepsin G, and proteinase 3) in relation to acute ischemic stroke (AIS) outcomes and in relation to the outcomes of patients treated with intravenous recombinant tissue plasminogen activator (IV-rtPA). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Within 30 minutes of onset, the in ammation began to respond and neutrophils increased in circulating [9]. A large prospective study suggested that elevated levels of plasma neutrophil elastase obtained upon admission were associated with adverse neurological outcomes at 3 months after receiving intravenous thrombolysis for AIS, which was released by neutrophils [20]. Intravenous thrombolysis therapy could partially restore blood ow in ischemic penumbra and minimized brain tissue damage, while the immune system may still maintain an in ammatory response after vascular recanalization [21].…”
Section: Discussionmentioning
confidence: 99%
“…Within 30 minutes of onset, the in ammation began to respond and neutrophils increased in circulating [9]. A large prospective study suggested that elevated levels of plasma neutrophil elastase obtained upon admission were associated with adverse neurological outcomes at 3 months after receiving intravenous thrombolysis for AIS, which was released by neutrophils [20]. Intravenous thrombolysis therapy could partially restore blood ow in ischemic penumbra and minimized brain tissue damage, while the immune system may still maintain an in ammatory response after vascular recanalization [21].…”
Section: Discussionmentioning
confidence: 99%